Farewelling the dead in Roman Egypt: an analysis of funeral portraits (1st Century) - Ladeira Santana, Jéssica (Romanitas - Revista de Estudos Grecolatinos, 2026)
The objective of this article is to present how Egyptians understood death and represented their identities in the first century. In this sense, we seek to reflect on the conception of dying in Roman Egypt through the myths and mortuary practices preserved for millennia and adapted to make sense of the historical and social context. Furthermore, we seek to understand the negotiations carried out by members of the chora elite, who represented themselves with symbols of Pharaonic Egyptian belief combined with Greco-Roman elements in funerary portraits.
Keywords: Roman Egypt; Death; Identity; Funeral portraits